Design of skis with non-tailored snow interaction: A reverse commercial approach - Sancho, J.; Sancho, A. (Science and Skiing VII, 2018)
In conclusion, a reverse approach with a non-tailored model of the interface between a turning ski and the snow has been developed and first presented in this paper. Despite having many potential advantages for its universality, this approach still needs much work to improve its ease of use. Results are in accordance with those shown in other works, but more models and parameters are still under investigation for reaching even better results and faster calculations. A more-detailed evaluation of the mechanical response of the ski structure - including dynamic analysis and damping materials inside (Himayat, Harland, & Silberschmidt, 2015) - is being carried out between Boreas and the State University of Navarra.